Parathyroidectomy Is Associated with Reduced Mortality in Hemodialysis Patients with Secondary Hyperparathyroidism - Ma, Tsung-Liang (Biomed Res Int, 2015)
Secondary hyperparathyroidism increases morbidity and mortality in hemodialysis patients. The Kidney Disease Outcomes Quality Initiative Guidelines recommend parathyroidectomy for patients with chronic kidney disease and parathyroid hormone concentrations exceeding 800 pg/mL; however, this concentration represents an arbitrary cut-off value. The present study was conducted to identify factors influencing mortality in hemodialysis patients with parathyroid hormone concentrations exceeding 800 pg/mL and to evaluate the effects of parathyroidectomy on outcome for these patients. Two hundred twenty-one hemodialysis patients with parathyroid hormone concentrations > 800 pg/mL from July 2004 to June 2010 were identified. 21.1% of patients (n = 60) received parathyroidectomy and 14.9% of patients (n = 33) died during a mean follow-up of 36 months. Patients with parathyroidectomy were found to have lower all-cause mortality (adjusted hazard ratio [aHR]: 0.34). Other independent predictors included age ≥ 65 years (aHR: 2.11) and diabetes mellitus (aHR: 3.80). For cardiovascular mortality, parathyroidectomy was associated with lower mortality (HR = 0.31) but with a marginal statistical significance (p = 0.061). In multivariate analysis, diabetes was the only significant predictor (aHR: 3.14). It is concluded that, for hemodialysis patients with parathyroid hormone concentrations greater than 800 pg/mL, parathyroidectomy is associated with reduced all-cause mortality.